KOMPILASI HUKUM ISLAM DALAM PERPEKTIF HUKUM PERUNDANG-UNDANGAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study analyses the problematic position of Presidential Instruction 1/1991 within Indonesian legislation system after the enactment of Act 10/2004. It also finds that religious court judges still base their decision on Compilation of Islamic Law.Apparently, CIH is regarded as a living law and as an Indonesian fiqh.